Azimuthal Variation in the Io Plasma Torus Observed by the Hisaki Satellite From 2013 to 2016. Issue 5 (15th May 2019) - Tsuchiya, F.; Arakawa, R.; Misawa, H.; Kagitani, M.; Koga, R.; Suzuki, F.; Hikida, R.; Yoshioka, K.; Steffl, A.; Bagenal, F.; Delamere, P.; Kimura, T.; et al.
Abstract: In the Jovian magnetosphere, sulfur and oxygen ions supplied by the satellite Io are distributed in the so‐called Io plasma torus. The plasma torus is located in the inner area of the magnetosphere and the plasma in the torus corotates with the planet. The density and the temperature of the plasma in the torus have significant azimuthal variations. In this study, data from three‐year observations obtained by the Hisaki satellite, from December 2013 to August 2016, were used to investigate statistically the azimuthal variations and to find out whether the variations were influenced by the increase in neutral particles from Io. The azimuthal variation was obtained from a time series of sulfur ion line ratios, which were sensitive to the electron temperature and the sulfur ion mixing ratio S 3+ /S + . The major characteristics of the azimuthal variation in the plasma parameters were consistent with the dual hot electron model, proposed to explain previous observations. On the other hand, the Hisaki data showed that the peak System III longitude in the S 3+ /S + ratio was located not only around 0°–90°, as in previous observations, but also around 180°–270°. The rotation period, the System IV periodicity, was sometimes close to the Jovian rotation period. Persistent input of energy to electrons in a limited longitude range of the torus is associated with the shortening of the System IV period. Key Points: Persistent azimuthal variations in the Io plasma torus were confirmed from three years of Hisaki observations The characteristics of the azimuthal variation were consistent with the dual hot electron model but different behaviors were also found The System IV period decreased 3 times. Two of these decreases were associated with increased volcanic activity on Io